2015
DOI: 10.1007/s10578-015-0562-y
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Parameters in Children and Adolescents with Attention-Deficit/Hyperactivity Disorder

Abstract: The aim of this study is to compare iron deficiency parameters in patients with stimulant-naive attention-deficit/hyperactivity disorder (ADHD) and healthy controls, to investigate whether there are differences among the ADHD presentations, and to evaluate the relationship between ADHD symptom severity and serum ferritin levels. In addition, ADHD-Predominantly Inattentive (ADHD-PI) patients with restrictive hyperactivity/impulsivity symptoms were evaluated as a separate group with "restrictive inattention pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 51 publications
0
25
0
3
Order By: Relevance
“…The number of participants varied across studies, and ranged from 27 to 1260. Four studies were conducted in Europe [8, 13, 14, 18], one in the USA [11], one in Egypt [19], one in Brazil [20], and four in Asia [10, 2123]. With the exception of three studies [8, 22, 23], all included studies reported medication use in the patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of participants varied across studies, and ranged from 27 to 1260. Four studies were conducted in Europe [8, 13, 14, 18], one in the USA [11], one in Egypt [19], one in Brazil [20], and four in Asia [10, 2123]. With the exception of three studies [8, 22, 23], all included studies reported medication use in the patients.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Adisetiyo et al [11] found that medication-naïve patients with ADHD had lower estimated brain iron in the striatum and thalamus than did healthy controls. However, other authors have failed to find a relationship between serum ferritin and ADHD [1214]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the results of the case control studies searching ferritin levels differ from each other. Donfrancesco et al [18], Menegassi et al [19] and Perçinel et al [17] did not find significant differences in ferritin levels between groups. On the contrary, some other studies detected lower ferritin levels in ADHD subjects [12,44,45].…”
Section: Discussionmentioning
confidence: 95%
“…We found a positive correlation between psychosomatic subscale of CPRS and ferritin. Other studies reported the relationship between the ADHD hyperactivity scores on Conners scale and low ferritin levels in their ADHD group [15][16][17]. Moreover, the results of the case control studies searching ferritin levels differ from each other.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation